KONDISI SOSIAL EKONOMI KELUARGA PASCA PEMUTUSAN HUBUNGAN KERJA (Studi Kasus Industri Tekstil di Kecamatan Dayeuhkolot-Kabupaten-Bandung-Jawa Barat) - Abu Hanifah; Suyanto Suyanto (Sosio Konsepsia, 2010)
This was a case studies research done by using qualitative approach. This research was done in Kabupaten Dayeuhkolot specifically targeting Desa Cangkuang Wetan, Desa Citeureup, and Desa Pasawahan. The problem faced by the families of those who got a Termination of Employment was that they cannot meet their minimum basic needs because the companies have not paid their severance. To overcome these problems, the-i; are forced to borrow some money from relatives, friends and neighbors. Potentials owned by the victims of the termination of employment is that most of them still in their productive age and have the skills that allow for them to find new jobs that match the skills they have. There are several environment potency than can be used to overcome the problems faced by the victims of termination ofÂ employment some of them are the availability of various types of companies that allow for them to apply for a job. In addition Kabupaten Dayeuhkolot residents who are predominantly Muslim is a potential source if it can be resusticated to carry out their responsibility to pay zakat and/alms managed through Rumah Zakat. It is very possible considering the kinship system in this area is very close and interwoven relationshipbetween citizens fairly intensively through existed social organizations or associations of local government. The local government is commited enough to solve this problem, of which, Office of Industry and the Department of Manpower and Transmigration has conducted skills training to victims of termination ofÂ employmentand trying to distribute them to work in companies thet exist in this area. Besides, there are thoughts of the District government to implement empowerment programs for the familes of those who got a termination of employment in Dayeuhkolot.